The effect of perceptual decision-making on the interpretation of twin fetal heart rate tracings. (3rd June 2022) - Ploran, Elisabeth J.; Soni, Shelly; Snellings, Jackson T.; Rausch, Andrew; Rochelson, Burton
Abstract: Objective: Decision-making is an integrative process during which multiple sources of available evidence are combined into a singular response. Importantly, subconscious processes occur in perceptual decisions that may influence interpretations of visually displayed data such as fetal heart rate tracings (FHRT), which are typically presented together for twins. To examine the potential impact of subconscious perceptual influences on fetal well-being, differences in assessments of FHRTs for twin gestations presented singly or paired were evaluated for baseline fetal heart rate, variability, accelerations, decelerations, and overall concern. Study design: Obstetrical nurses ( N = 27) assessed FHRTs from 20 twin gestations (each of which had at least one live birth with a 5-min Apgar <7) presented either on the same tracing or as singletons on separate tracings. Nurses were naïve to the fact that the fetal heart rate tracings presented in the unpaired condition were the same as those presented in the paired condition. Assessments were then compared between the two conditions. Results: Each nurse participant completed ratings on five metrics for each of 20 twin gestations across two conditions (80 FHRT assessments, 400 metrics total per participant). The intraobserver impact of visual context was calculated as the frequency of changed opinions regarding an individual metric (e.g. variability) between the paired and unpaired contexts for each individual fetal heart rate. Assessments of variability (average Kappa = 0.59), decelerations (average Kappa = 0.34), and overall level of concern (average Kappa = 0.33) were moderately to heavily impacted by viewing condition (unpaired vs. paired FHRT). Analysis of interobserver agreement using intraclass correlations (two-way random effect, absolute agreement) indicates poor agreement on unpaired assessments for both accelerations (ICC = 0.01, 95% CI −0.01–0.04) and decelerations (ICC = 0.22, 95% CI 0.15–0.33). These results are mirrored in poor agreement on paired assessments for both accelerations (ICC = 0.00, 95% CI −0.01–0.03) and decelerations (ICC = 0.27, 95% CI 0.19–0.39). There was moderate agreement on overall level of concern for unpaired assessments (ICC = 0.55, 95% CI 0.44–0.67) and near moderate agreement for the paired condition (ICC = 0.45, 95% CI 0.34–0.58). Conclusions: The simultaneous presentation of fetal heart rate tracings in twin gestations introduces both intraobserver and interobserver variances in the interpretation of variability, accelerations, and decelerations, likely due to the influence of subconscious perceptual decision-making. This may theoretically affect outcomes in cases in which visual information is nuanced. More research is necessary to determine whether the standard protocol of simultaneous assessment of FHRT in twins is subliminally affected by perceptual decision-making.